VD_FINDINFO Jug / 2016 / 66 vom 27. Oktober 2015 - VD Tribunal cantonal (2015)
APPRÉCIATION DES PREUVES, CONSTATATION DES FAITS, ABUS DE CONFIANCE, FIXATION DE LA PEINE | 138 ch. 1 al. 2 CP, 47 CP, 70 al. 1 CP, 126 CPP (CH), 428 al. 1 CPP (CH), 429 CPP (CH), 442 al. 4 CPP (CH)